2021
DOI: 10.1038/s41380-021-01377-7
|View full text |Cite|
|
Sign up to set email alerts
|

Microglial ERK-NRBP1-CREB-BDNF signaling in sustained antidepressant actions of (R)-ketamine

Abstract: Abstract(R,S)-ketamine elicits rapid-acting and sustained antidepressant actions in treatment-resistant patients with depression. (R)-ketamine produces longer-lasting antidepressant effects than (S)-ketamine in rodents; however, the precise molecular mechanisms underlying antidepressant actions of (R)-ketamine remain unknown. Using isobaric Tag for Relative and Absolute Quantification, we identified nuclear receptor-binding protein 1 (NRBP1) that could contribute to different antidepressant-like effects of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(60 citation statements)
references
References 80 publications
1
42
0
Order By: Relevance
“…Nucleic acid-based therapeutics represent a promising technology platform to manipulate gene targets. Previously reported a new nucleic acid drug named cholesterol conjugated DNA/RNA heteroduplex oligonucleotide (HDO) [27]. The HDO carried cholesterol leading to ASO accumulation in the liver and was more potent at reducing the expression of target mRNA in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleic acid-based therapeutics represent a promising technology platform to manipulate gene targets. Previously reported a new nucleic acid drug named cholesterol conjugated DNA/RNA heteroduplex oligonucleotide (HDO) [27]. The HDO carried cholesterol leading to ASO accumulation in the liver and was more potent at reducing the expression of target mRNA in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…7A). Notably, the HDO carried cholesterol leading to ASO accumulation in the liver and was more potent at reducing the expression of TBK1 mRNA in the liver [27,28] (Fig. 7B).…”
Section: Tbk1-hdo and Pharmacological Inhibition Of Tbk1 Reduce Cca C...mentioning
confidence: 99%
“…More importantly, especially in the context of this review, MeCP2 S421 phosphorylation can be induced by early life stress in neurons of the parvocellular hypothalamic PVN [ 94 ], the previously described center of stress regulation. Moreover, antidepressant drugs such as imipramine, fluoxetine, or ketamine can induce S421 phosphorylation and reverse stress-induced depression, which will be discussed in the next section of this review [ 95 , 96 , 97 ].…”
Section: Mecp2 and Synaptic Plasticitymentioning
confidence: 99%
“…Finally, a recent study using a chronic social defeat stress model reported that the fast-acting antidepressant effects of (R)-ketamine, the enantiomer of the FDA-approved antidepressant (S)-ketamine, was mediated by the increased BDNF transcription. Such an increase resulted from the activation of CREB and MeCP2 suppression in microglia [ 97 ].…”
Section: Mecp2 and Stress-related Pathology: Focus On Depressionmentioning
confidence: 99%
“…It is also a key target of antidepressants and serves to transduce their molecular signaling actions (Barbiero et al, 2007 ; Adaikkan et al, 2018 ). In partnership with CaMKIV, it can regulate CREB, a transcription factor of major interest in antidepressant activity (Blendy, 2006 ; Yao et al, 2021 ). Activation of CREB would result in increased BDNF transcription and further amplify the cascade.…”
Section: Reviewmentioning
confidence: 99%